2005
DOI: 10.1038/sj.bjc.6602460
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of tumour-associated antigens in hepatocellular carcinoma

Abstract: To identify tumour and tumour-associated antigens in patients with hepatocellular carcinoma (HCC) one may find potential diagnostic markers and immunotherapeutic targets. In the current study, 30 distinct antigens reactive with serum IgG from HCC patients were identified by serological analysis of cDNA expression libraries (SEREX). The mRNA expression patterns of 14 of these 30 antigens were altered in cancer as further revealed by cDNA microarray, with upregulation for nine and downregulation for five antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 40 publications
5
65
0
Order By: Relevance
“…Consistent with recent studies demonstrating overexpression of PcG genes in cancer (Vonlanthen et al, 2001;Sellers and Loda, 2002;Kleer et al, 2003;Raaphorst et al, 2003;Breuer et al, 2004;Kim et al, 2004;Shi et al, 2005), we found that both BMI-1 and EZH2 are strongly expressed by a variety of tumours (Table 3; Supplementary Material; Figure 1). This broad upregulation in cancer makes them attractive immunotherapeutic targets for malignant disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with recent studies demonstrating overexpression of PcG genes in cancer (Vonlanthen et al, 2001;Sellers and Loda, 2002;Kleer et al, 2003;Raaphorst et al, 2003;Breuer et al, 2004;Kim et al, 2004;Shi et al, 2005), we found that both BMI-1 and EZH2 are strongly expressed by a variety of tumours (Table 3; Supplementary Material; Figure 1). This broad upregulation in cancer makes them attractive immunotherapeutic targets for malignant disease.…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies suggest that they also contribute to the development of cancer in humans. Aberrant PcG protein expression, such as overexpression, failure of downregulation or coexpression, has been reported in Hodgkin's lymphoma , B-cell lymphoma , mantle cell lymphoma (Bea et al, 2001;Visser et al, 2001), prostate cancer (Sellers and Loda, 2002;Varambally et al, 2002), breast carcinoma (Kleer et al, 2003;Raaphorst et al, 2003;Kim et al, 2004), HCC (Shi et al, 2005) and during lung carcinogenesis (Vonlanthen et al, 2001;Breuer et al, 2004). Some of these altered patterns of expression may be of diagnostic and prognostic relevance (Varambally et al, 2002;Raaphorst et al, 2003;Breuer et al, 2004;Kim et al, 2004).…”
mentioning
confidence: 99%
“…Transgelin has been shown to bind to and colocalize with F-actin, indicating that it may be involved in cell differentiation by stabilizing the cytoskeleton through actin binding, 12,13 and diminished expression of this protein has been reported in a variety of cell types on transformation [14][15][16] as well as in several human cancers, including lung, renal, prostate and breast cancer. 14,[17][18][19] According our current knowledge, there are few reports on its role in progression of colorectal cancer.…”
mentioning
confidence: 99%
“…5D), implying that the overexpression of TAGLN2 could only be partially ascribed to the DNA amplification because there might be multiple mechanisms C18 C05 C35 C04 C09 C06 C24 C51 C16 C19 C08 C39 C21 C28 C10 C27 C41 C11 C23 C30 C02 C03 C12 C07 C14 C20 C34 C22 C13 C32 C26 C38 C36 C37 C17 C31 C29 C33 C40 C01 C12 C28 C03 C07 C08 C09 C05 C02 C10 C22 C14 C23 C30 C17 C16 C13 C15 C21 C11 C01 C09 C18 C22 C40 C19 C41 C38 C26 C23 C24 C29 C21 C36 C08 C17 C25 C04 C11 C05 C37 C32 C06 C30 C31 C33 C02 C34 C14 C28 C07 C03 C12 C16 C27 C10 C20 C39 C13 C15 C35 C01 C13 C15 C28 C07 C08 C03 C05 C12 C10 C02 C09 C23 C14 C17 C16 C21 C22 C30 involved in the upregulation of TAGLN2. In addition, some reports indicated that TAGLN2 was also overexpressed in gastric cancer [34] and HCC [42], where TAGLN2 was even considered as a diagnostic marker for HCC. However, very little is known about the actual effect of TAGLN2 on hepatocarcinogenesis and tumor progress.…”
Section: Tagln2 Involving Chromosome 1q21 In Hccmentioning
confidence: 99%